Nutrient Deficiency Symptoms of Woody Ornamental Plants in South Florida - Timothy K. Broschat (EDIS)
ENH-1098, a 5-page illustrated fact sheet by Timothy K. Broschat, describes and illustrates typical symptoms for common nutrient deficiencies in trees and shrubs grown in south Florida landscapes. Published by the UF Department of Environmental Horticulture, March 2008.